DIRECT COSTING AND THE LAW. - Hirschman, Robert W. (The Accounting Review, 1965)
Abstract The purpose of this article is not to discuss the arguments for or against the use of direct costing. It is instead to locus attention on some of the legal implications a company should keep in mind with respect to taxation, securities regulation, and antitrust and other legislation if it is considering the use of direct costing as an all purpose accounting technique. Advocates of direct costing maintain that it simplifies the interpretation of financial results and that it is particularly useful for profit planning, pricing decisions, and cost control. Opponents do not generally deny that the system has advantages, they are more concerned with its application to external reporting. The National Association of Accountants reported that seventeen of the fifty companies participating in a research study report used direct costing in preparing financial statements for stockholders. In none of these cases had auditors given a qualified opinion or taken exception to the practice. Apparently the CPAs performing the examination believe that the use of direct costing results in financial statements which present fairly both the financial positions of their clients as well as the results of operations for the periods under review.